Body size and body composition effects on heat loss from the hands during severe cold exposure. Issue 2 (11th February 2018) - Payne, Stephanie; Macintosh, Alison; Stock, Jay
Abstract: Objectives: This study investigated the influence of body size and composition on maintaining hand temperature during severe cold exposure. The hand's high surface area‐to‐volume ratio predisposes the hand to heat loss, increasing the risk of cold injury and even hypothermia, which are major selective pressures in cold environments. While vasoregulation may reduce heat loss from the hand, the effect of body form, tissue thermogenesis, and body insulation on heat loss is unknown. Materials and Methods: Thermal imaging was used to determine heat loss during a 3‐min ice‐water hand immersion test carried out on 114 volunteers (female = 63, male = 51). Established anthropometric measures were used to quantify body size, and bioelectrical impedance analysis determined skeletal muscle and fat mass. Results: Skeletal muscle mass relative to body mass was a highly significant predictor of heat loss, while body mass, fat mass, and stature were not. Body composition and body size had little to no significant influence during rewarming after immersion. Discussion: The thermogenic properties of muscle mass support maintenance of hand temperature during severe cold exposure. The findings here suggest that muscular individuals are less susceptible to heat loss and cold injury, and may be better at manual tasks in cold conditions than nonmuscular individuals.